The Urgency Of Establishing Sharia Economic Law (Omnibus Law) In Increasing Sharia Economic Development In Indonesia - Hardi Fardiansyah; Rio Christiawan; Tuti Widyaningrum (Jurnal Hukum dan Kenotariatan, 2023)
The non-maximum development of Indonesia's shari'ah economy has become a joint work for the Government, KNEKS, and Muslims in Indonesia. Based on data quoted from GIEI (Global Indicator Economic Islam), Indonesia is in sixth place in the finance sector under Kuwait and the United Arab Emirates, second in the halal food sector under Malaysia, not in the top 10 in the travel sector, third in the fashion sector, not in the top ten in the pharma & cosmetics sector, and not in the world's top 10 in the media and leisure sector. Even though Indonesia is a country that has the largest Muslim population in the world, it means that this country has great potential to develop more rapidly. In the opinion of researchers, the most fundamental problem is the not-yet optimal development of the shari'ah economy in Indonesia, namely because there are still many regulations that overlap with each other, and many sectors still need to be appropriately covered. The findings of the authors, currently Indonesia only has four rules at the level of laws governing the Islamic economic sector, namely the Islamic banking law, the Islamic capital market law, halal food and beverages, and ZISWAF (Zakat Infaq Shodaqoh Wakaf). Many sectors have yet to be well covered, such as Sharia financing, export financing, and pensions. Accordingly, the function of the CIPTAKER law is to harmonize one regulation with another and cover sectors that need to be appropriately regulated. The formation of the Sharia Economic Law using the omnibus law concept is believed to enhance the development of the Sharia economy in Indonesia. The results of this study indicate that the presence of a shari'ah economic law using the omnibus law concept has a critical urgency in increasing the shari'ah economy in Indonesia, particularly in aligning the shari'ah econnomic sector, which has not been integrated and comprehensively regulating the shari'ah economic sector which has not been completely held.; Omnibus Law. Keywords: Urgency, Sharia, Economic, Omnibus Law